Pengaruh Citra Merek dan Promosi terhadap Keputusan Pembelian Layanan IndiHome pada PT Global Bahana Karya Garut - Taofik Hidayat; Seliana Nurdianty (Journal of Innovative and Creativity (Joecy), 2026)
The increasingly intense competition in the telecommunications industry requires companies to establish a strong brand image and implement effective promotional strategies to enhance consumers' purchasing decisions. This study aims to examine the influence of brand image and promotion on the purchasing decisions of customers at PT Global Bahana Karya Garut. The research employed a quantitative approach with an associative research design. The sample consisted of 68 customers selected using a purposive sampling technique. Data were collected through a structured questionnaire and analyzed using descriptive statistics, validity and reliability tests, Spearman rank correlation analysis, coefficient of determination, t-test, and F-test with the assistance of IBM SPSS Statistics version 26. The findings indicate that brand image has a positive and significant relationship with purchasing decisions, with a correlation coefficient of 0.748, while promotion also demonstrates a positive and significant relationship with purchasing decisions, with a correlation coefficient of 0.688. Simultaneously, brand image and promotion exhibit a very strong relationship with purchasing decisions, with a multiple correlation coefficient of 0.842, explaining 71.0% of the variance in purchasing decisions. These findings suggest that strengthening brand image, supported by effective promotional strategies, plays a crucial role in enhancing customers' purchasing decisions. Therefore, companies should continuously optimize brand image management and promotional activities to improve competitiveness and maintain customer loyalty.